Menedżerowie i mafiosi: etyka motywowania w autobiografich "self-made manów" - Szukała, Michał (Annales. Etyka w Życiu Gospodarczym, 2015)
The paper is an attempt to verify the assumptions of the motivation-hygiene theory by Frederick Herzberg in the context of the values and practices of leading managers of the U.S. economy. The two-factor theory is a part of every synthesis of management science, although its assumptions raise serious controversies. The subject matter of the analysis is the biographies of the most prominent managers, such as Henry Ford, Lee Iacocca, Walter P. Chrysler and Jordan Belfort (known as the ‘Wolf of Wall Street’). The basic aim of the analysis is to check their biographical story in the context of their motivation issues. The selection of characters has been imposed by the feature of being self-made men. It seems that their descriptions of how to motivate employees may be interpreted as a specific manifestation of values important to them in the perception of economic life and the interpersonal relations in structures of corporations functioning in different market circumstances. The choice of source materials from different historical moments and different economic spheres shows a conversion of values and goals in the American economy. One of the results of the analysis is the observation that Herzberg’s theory does not reflect the multiplicity of factors that may have a significant impact on the motivation of employees to perform their duties as well as possible. One of the aims of the discussion is to indicate the unusual source material, considered by many researchers as anecdotal, as potentially attractive for analyses in the field of the management sciences.